Flexural properties of silane treated cenosphere filled polypropylene: article - Ratiman, Muhammad Rais (2017)
The growing concern about the pollution by fly ash residue resulting from the generation of electricity at thermal power plant, has spurred development of fly ash for positive uses such as in cementations products, construction areas such as highway road bases, grout mixes and stabilizing clay based building materials. However, cenosphere usage are still insignificant compared to production of it. Cenosphere can be utilize more in plastic industry as their filler in the polymer. This paper study the effect of the cenosphere as plastic filler to the flexural strength of the composite. This study will give the opportunity to cenosphere to be used in plastic industry. The composite flexural modulus increases as the weight fraction of cenosphere is added. The silane treatment resulted in considerable improvement in the impact strength and density of the composites.